Experimental investigation of PV/T and thermoelectric systems using CNT/ water nanofluids - Abesh Ahmadlou, Leila; Najafi, Gholamhassan; Loni, Reyhaneh; Kasaeian, Alibakhsh Bakhash; Rizalman, Mamat; Mohd Fairusham, Ghazali; Arman, Abdullah; Ei-Shafy, A. S.; Mousa, Mohamed (Elsevier Ltd, 2023)
This study investigated experimentally the thermal performance of a Photovoltaic-thermal (PV/T) and thermoelectric (TE) system using the application of two nanofluids. Single-walled Carbon nanotube/water (SWCNT/water) and multi-walled Carbon nanotube/water (MWCNT/water), with a mass fraction of 0.02% were assessed as the working fluid of the PV/T system. Examinations were done from 10:00 to 16:30 daily in November 2021 at Tarbiat Modares University, Tehran, Iran. Different parameters were measured during the experimental tests including fluid inlet and outlet temperatures, volume flow rate, solar irradiance, and ambient and cell surface temperatures. The results showed that the highest performance of the solar system was measured using the application of SWCNT/water nanofluid. The PV/T surface temperature decreased using nanofluids compared to pure water. It was found that the output generated power and efficiency improved using nanofluid application whereas application of SWCNT/water was more effective compared to MWCNT/water nanofluid. Also, the application of the two nanofluids improved the performance of the TE module compared to pure water. The highest values of TE electric current, voltage, generated power, and efficiency were obtained using the application of SWCNT/water nanofluid.